Effect of alloying (V, Fe, Ge) additions on microstructural evolution in Ti-6Al-4V-based alloys after hot rolling and annealing - K.N. Chaithanya Kumar; K.S. Suresh (Journal of Alloys and Metallurgical Systems)
Ti-6Al-4V is the most widely used titanium alloy due to its ability to achieve balanced mechanical properties through microstructural modification via thermomechanical processing. Alloying elements in Ti-6Al-4V play critical roles in stabilizing the β-phase and influencing deformation-induced phase transformations. This study investigates the effects of V, Fe, and Ge additions on the microstructure and phase stability of Ti-6Al-4V under subjected to hot rolling and annealing at different temperatures. Alloys with nominal compositions Ti-6Al-4V, Ti-6Al-5V, Ti-6Al-5V-1Fe, and Ti-6Al-5V-1Fe-2Ge (in wt%) were synthesized via vacuum arc melting and subjected to hot rolling and annealing at sub-transus temperatures. XRD and EBSD analyses revealed significant modifications in the morphology, phase distribution, and phase fractions of α and β phases, with β-phase content increasing with alloying additions. Hot rolling promoted deformation-induced dynamic transformation of α to β phase, except in the Ge-containing alloy, which demonstrated its role as a suppressor of dynamic transformation. Fe and Ge additions reduced β-phase fragmentation during hot rolling, while annealing facilitates static recovery, recrystallization and phase stability. Ge acts as a neutral stabilizer in Ti alloys, reduces the transformation temperature and suppresses the transformation dynamics. A strong variant selection was observed in the transformed β region of Ge-added samples, influencing microstructural evolution. This study demonstrates the influence of alloying elements on hot deformation, elemental distributions, phase transformations, and equilibrium phase fractions, providing insights into tailoring microstructures of Ti-6Al-4V through thermomechanical processing.